Moral Values in Short Stories Di Ujung Senja and its Implications for Learning Bahasa Indonesia in High School - Afan Al Fatikhi Nasukha (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The erosion of moral values ​​in Indonesian society lately is very alarming, especially since this is happening among students or at school level. As we already know, the behavior of students today is increasingly becoming more and more, many of the students are immoral, even there are those who dare to fight their own teacher. Instilling moral values ​​can be inserted through language and literary learning, one of the ways that can be used is by reading short stories that contain a lot of moral values. This study aims to analyze the types and forms of moral values ​​that exist in a collection of short stories titled In Ujung Senja. This analysis uses a qualitative descriptive approach that is by reading as a whole and identifying it. Retrieval of data in this study by reading and recording sentence fragments or fragments of discourse included in the moral values ​​sought by researchers. That way the moral values ​​contained in the short story are easily identified. Based on the analysis of a collection of short stories in Ujung Senja, the requirements for moral values ​​are appropriate to apply, because in this short story collection contains many moral values, namely praying, being grateful, obedient, trusting, responsibility, generous, honest, hard working, apologizing, mutual respect, and please help and serve both parents. This value was identified from several events and characters in the short story. Abstrak Tergerusnya nilai moral pada masyarakat indonesia akhir-akhir ini sangat memprihatinkan, apalagi hal ini terjadi pada kalangan pelajar atau tingkatan sekolah. Seperti yang sudah kita ketahui, tingkah laku pelajar di masa sekarang semakin menjadi-jadi, banyak dari pelajar yang tidak bermoral, bahkan sampai ada yang berani melawan gurunya sndiri. Penanaman nilai moral dapat disisipkan melalui pembelajaran bahasa dan sastra, salah satu cara yang bisa digunakan adalah dengan membaca cerpen yang banyak mengandung nilai moral. Penelitian ini bertujuan untuk menganalisis jenis dan wujud nilai moral yang ada pada kumpulan cerita pendek yang berjudul Di Ujung Senja. Analisis ini menggunakan pendekatan deskriptif kualitatif yaitu dengan membaca secara keseluruhan serta mengidentifikasinya. Pengambilan data pada penelitian ini dengan cara membaca dan mencatat penggalan kalimat atau penggalan wacana yang termasuk ke dalam nilai moral yang dicari peneliti. Dengan begitu nilai moral yang terkandung dalam cerita pendek tersebut mudah diidentifikasi. Berdasarkan hasil analisis kumpulan cerpen Di Ujung Senja syarat akan nilai moral yang patut untuk diterapkan, karena dalam kumpulan cerpen ini banyak memuat nilai-nilai moral yaitu berdoa, bersyukur, taat, tawakal, tanggung jawab, dermawan, jujur, kerja keras, meminta maaf, saling menghormati, dan tolong menolong serta berbakti kepada kedua orang tua. Nilai tersebut teridentifikasi dari beberapa kejadian dan tokoh dalam cerita pendek tersebut. Kata kunci: jenis dan wujud nilai moral dalam kumpulan cerpen